The Determinants of Trust in Supplier-Automaker Relationships in the U.S., Japan and Korea - Dyer, Jeffrey H.; Chu, Wujin (Journal of International Business Studies, 2000)
We examine the determinants of trust in 453 supplier-automaker relationships in the U.S., Japan, and Korea. We define trust and derive a model of its determinants drawing upon (1) an embeddedness (relationship-based) perspective, (2) a process-based perspective, and (3) an economic (hostage-based) perspective. Our findings indicate strong support for the process-based perspective in all countries; embeddedness was only important in Japan, and the economic hostage-based variable (stock ownership) was not important in any country.